Sistem Pakar Cara Mendidik Anak Pelajaran Agama Islam Sesuai Al-Qur'an Menggunakan Metode Forward Chaining - Maulidan, Farid; Dwi Suhendra, Christian; Juita, Ratna (Politeknik Negeri Batam, 2023)
The Al-Qur'an indirectly provides methods for educating children from an early age, as listed in Al-Ahqaf [46]: 30. The implementation of these educational methods requires an expert, specifically an Islamic religious teacher who can suggest appropriate methods to use. Hence, in this context, there is a need to develop an expert system application that can assist teachers in recommending suitable educational methods to parents or guardians based on the child's behavior input. The